LncRNA NEAT1 Interacted With DNMT1 to Regulate Malignant Phenotype of Cancer Cell and Cytotoxic T Cell Infiltration via Epigenetic Inhibition of p53, cGAS, and STING in Lung Cancer - Ma, Fang; Lei, Yi-Yu; Ding, Meng-Ge; Luo, Li-Hua; Xie, Yang-Chun; Liu, Xian-Ling (Frontiers in Genetics, 2020)
Purpose: Lung cancer is the main cause of cancer-related mortality worldwide. We report here the biological role of Nuclear paraspeckle assembly transcript (NEAT)1 in the pathogenesis of lung cancer and the underlying mechanisms. Methods: Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting analysis was used to evaluate expression of mRNA and protein. RNA immunoprecipitation (RIP) assay, chromatin immunoprecipitation (CHIP) followed by qPCR analysis and reporter assay were used to detect DNA/RNA and protein binding. Tumor-infiltrating lymphocytes (TILs) were assessed with Haematoxylin Eosin (HE) staining. Cytotoxic T cell infiltration was evaluated with flow cytometric analysis and Immunohistochemistry (IHC) staining. The changes of cell viability, cell invasive and migratory ability was analyzed by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide), colony formation and transwell assays, respectively. Syngeneic tumor model was setup to evaluate tumor growth. Results: The results showed that NEAT1 was overexpressed in lung cancer tissues and cancer cell lines. This aberrant expression was closely related with tumor stage and lymph node metastasis. Tumor sample with highCD8+ showed lower NEAT1 expression. In vitro studies displayed that inhibition of NEAT1 with shRNA resulted in suppression of survival and migration/ invasion of lung cancer cells; On the other side, NEAT1 was found to promote tumor growth via inhibiting cytotoxic T cell immunity in syngeneic models. Finally, NEAT1 was found to interact with DNMT1, which in turn inhibit P53 and cGAS/STING expression. Conclusions: Our findings demonstrated that NEAT1 interact with DNMT1 to regulate cytotoxic T cell infiltration in lung cancer via inhibition of cGAS/STING pathway. The results provided the novel mechanistic insight into the pathogenesis of lung cancer.